A Comparative Study of Montessori and Traditional Education Approaches: Cognitive Development and Academic Achievement - Mutmainna, Nurunnisa; Rizqi, Vini; Halim, Chandra; Astuti, Peni (International Education Trend Issues, 2024)
This study investigates the comparative impacts of Montessori and traditional education approaches on cognitive development, academic achievement, and social-emotional skills among primary school students. Employing a mixed-methods design, the research involved 500 students aged 6 to 12 years from both educational settings. Quantitative data were collected through standardized assessments, while qualitative insights were gathered via interviews with teachers, parents, and students. The results revealed that Montessori students demonstrated significantly higher cognitive development, particularly in processing speed, working memory, and perceptual reasoning. Additionally, Montessori students outperformed their peers in traditional schools in mathematics and language arts, though no significant difference was found in science achievement. Social-emotional skills, including social competence and behavioral self-control, were also more developed in Montessori students. Qualitative findings highlighted the perceived benefits of the Montessori approach in fostering independence, creativity, and intrinsic motivation, while traditional education was noted for its structured curriculum and academic rigor. The study suggests that a hybrid educational model integrating elements of both Montessori and traditional methods could optimize educational outcomes, promoting both academic excellence and holistic development.